(D²-3DD'+2D'²)z=(2+4x)ex+2y.
"(D^{2}-3DD^{'}+2D^{'})z=(2+4x)e^{x+2y}"
Now , to solve this type of differential equation , we let the following terms of equation as -
"D=m\\ D^{'}=1"
Now the given Differential equation ,will be form as -
So Auxiliary equation will become as -
"=m^{2}-3m+2=0"
"=m^{2}-2m-m+2=0"
"=m(m-2)-1(m-2)=0"
"=(m-1)(m-2)=0"
So this is case where roots are different -
So CF can be written as -
"CF=f_{1}(y+x)+f_{2}(y+2x)"
Now PI of the Differential equation can be given as -
"PI=\\dfrac{1}{(D^{2}-3DD^{'}+2D^{'})}(2+4x)e^{x+2y}"
"PI=2\\dfrac{1}{(D^{2}-3DD^{'}+2D^{'})}e^{x+2y}+4\\dfrac{1}{(D^{2}-3DD^{'}+2D^{'})}xe^{x+2y}"
"PI=2\\dfrac{1}{(D^{2}-3DD^{'}+2D^{'})}e^{x+2y}"
Now , this is case of "\\phi(ax+by)" ";F(a,b)\\ {\\neq}0"
"PI=2\\dfrac{1}{(1^{2}-3(1)(2)+2(2)}\\iint e^{u}dudu"
"PI=-2e^{x+2y}"
Now PI of second function , we get -
"PI=4\\dfrac{1}{(D^{2}-3DD^{'}+2D^{'})}xe^{x+2y}"
Now , this is a case of "F(x,y)=e^{ax+by},V," where V is a function of "x" and y .
"PI=\\dfrac{1}{\\phi(D,D^{'})}e^{ax+by}.V=e^{ax+by}\\dfrac{1}{\\phi(D+a,D^{'}+b)}V"
"=e^{x+2y}" "\\dfrac{1}{((D+1)^{2}-3(D+1)(D^{'}+2)+2(D^{'}+2)}" "x"
"=e^{x+2y}\\dfrac{1}{D^{2}-D^{'}-4D-1}x"
"=e^{x+2y}\\dfrac{1}{D^{2}}[1-(\\dfrac{D^{'}}{D^{2}}+\\dfrac{4}{D}+\\dfrac{1}{D^{2}})]^{-1}x" "=\\dfrac {e^{x+2y}x^{3}}{6}"
Now complete solution is given as -
"z=CF+PI" "=f_{1}(y+x)+f_{2}(y+2x)+\\dfrac {e^{x+2y}x^{3}}{6}"
Comments
Leave a comment